2003
DOI: 10.1577/t01-076
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multimetric Index for Assessing the Biological Condition of the Ohio River

Abstract: The use of fish communities to assess environmental quality is common for streams, but a standard methodology for large rivers is as yet largely undeveloped. We developed an index to assess the condition of fish assemblages along 1,580 km of the Ohio River. Representative samples of fish assemblages were collected from 709 Ohio River reaches, including 318 ''leastimpacted'' sites, from 1991 to 2001 by means of standardized nighttime boat-electrofishing techniques. We evaluated 55 candidate metrics based on att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…By assessing the ecological status of this river site using pooled electrofishing and trawl catches and day and night electrofishing catches, respectively, it was concluded that electrofishing at night may substitute for additional sampling gears in large rivers (Figure 1; Wolter and Freyhof, 2004). Simon and Sanders (1999) and Emery et al (2003) arrived at a similar conclusion for the Ohio River. Erős et al (2008) reported that night electrofishing in the summer more than doubled the number of species collected by day electrofishing in the Danube River, Hungary; species richness curves were strongly flattening by day electrofishing 17-33 MWCW, but not by night electrofishing the same distance.…”
Section: Fishmentioning
confidence: 84%
See 1 more Smart Citation
“…By assessing the ecological status of this river site using pooled electrofishing and trawl catches and day and night electrofishing catches, respectively, it was concluded that electrofishing at night may substitute for additional sampling gears in large rivers (Figure 1; Wolter and Freyhof, 2004). Simon and Sanders (1999) and Emery et al (2003) arrived at a similar conclusion for the Ohio River. Erős et al (2008) reported that night electrofishing in the summer more than doubled the number of species collected by day electrofishing in the Danube River, Hungary; species richness curves were strongly flattening by day electrofishing 17-33 MWCW, but not by night electrofishing the same distance.…”
Section: Fishmentioning
confidence: 84%
“…Lyons, 1992a;Lazorchak et al, 2000;Hughes et al, 2002;Reynolds et al, 2003;Maret and Ott, 2004;Hughes and Peck, 2008), while others support the use of a fixed distance (Yoder and Smith, 1999;Emery et al, 2003;Flotemersch and Blocksom, 2005).…”
Section: Physically Based Site Lengthsmentioning
confidence: 99%
“…Average catch per unit of effort was highest in the lower group of sites (5.15 kg/hr), followed by upper (2.12 kg/hr) and middle (1.98 kg/hr) channels while number per unit of effort was higher in the upper channels (486 fish/hr), followed by lower (458 fish/hr) and middle (289 fish/hr) reaches. Intolerant species [12,13] comprised a greater percentage of the catch in the upper group, 16.7%, versus 11.1% for middle and 7.1% for lower groups of sites.…”
Section: Resultsmentioning
confidence: 99%
“…The most widely used methods were community-based approaches such as IBI (index of biological integrity) (Simon and Emery, 1995;Ganasan and Hughes, 1998;Lyons et al, 2001;Emery et al, 2003;Araújob et al, 2003;Long and Walker, 2005;TejerinaGarro et al, 2006;Pinto et al, 2006;Zhu and Chang, 2008), FBI (the fish-based index) (Oberdorff et al, 2002), TFC (the target fish community) (Meixler, 2011) and some other multiple-metric methods (Pont et al, 2006;Bergerot et al, 2008;Terra and Araújob, 2011). However, these methods have presented unique challenges (Simon and Sanders, 1999).…”
Section: Introductionmentioning
confidence: 99%